Effects of hot-air microwave rolling blanching pretreatment on the drying of turmeric (Curcuma longa L.): Physiochemical properties and microstructure evaluation. (1st January 2023) - An, Nan-nan; Lv, Wei-qiao; Li, Dong; Wang, Li-jun; Wang, Yong
Graphical abstract: Highlights: A new hot-air microwave rolling blanching was developed before drying of turmeric. Blanching effectively inactivated polyphenol oxidase and peroxidase. Blanching shortened drying time and improved quality of dried turmeric. The change of microstructure revealed the mechanism of quality improvement. Abstract: Blanching pretreatment can improve product quality and efficiency during food processing. Effects of hot-air microwave rolling blanching (HMRB) on physiochemical properties and microstructure of turmeric were investigated under various treatment times (0–10 min). Results showed that HMRB significantly changed weight, electrolyte leakage, texture, viscoelastic properties, pectin fractions content, thermal properties and drying quality of turmeric. Meanwhile, HMRB promoted the redistribution of water in turmeric and changed the cell structure, thus shortening drying time by 6.35–34.92 %. The polyphenol oxidase and peroxidase were entirely inactivated after blanching for 8 and 10 min, respectively. Compared with unblanched dried turmeric, the curcumin content, total phenolic, DPPH and ABTS were significantly increased by 20.76 %, 5.63 %, 7.54 % and 19.05 % at the optimal blanching time (8 min). Overall, HMRB can be used as a promising pretreatment technology to enhance the drying rate and improve the quality of dried turmeric.